Achieving sustainable food systems in a global crisis: Summary report - Bizikova, Livia; de Brauw, Alan; Rose, Mali Eber; Laborde Debucquet, David; Motsumi, Kulthoum; Murphy, Mike; Parent, Marie; Picard, Francine; Smaller, Carin (International Institute for Sustainable Development, 2023)
The world is not on track to achieve the United Nations Sustainable Development Goals by 2030. The prevalence of hunger and poverty—the two core goals which are the litmus test for everything else—are on the rise. This is being made worse by the Russian invasion of Ukraine, skyrocketing food, fertilizer, and energy prices, COVID-19, and climate change. In Africa, the situation is exacerbated by internal conflicts, political unrest, economic recessions, and swarms of desert locusts. To get back on track, it is critical to pursue policy pathways that encourage synergies and limit the trade-offs between hunger, poverty, nutrition, and climate change. This report summarizes the evidence-based and costed country roadmaps for effective public interventions to transform agriculture and food systems in Ethiopia, Malawi, and Nigeria in a way that ends hunger, makes diets healthier and more affordable, improves the productivity and incomes of small-scale producers and their households, and mitigates and adapts to climate change. The financing gap is immense. This report shows that while it is possible to achieve sustainable food system transformation in Ethiopia, Malawi, and Nigeria, in the next decade, it would require an average additional public investment of USD 10 billion per year from 2023 to 2030 and targeting spending on a more effective portfolio of interventions that achieve multiple sustainable development outcomes. Of the total USD 10 billion, the donor share averages USD 5.8 billion per year, and the country share averages USD 4.2 billion per year. Importantly, comparing the financing gap between the long-term investment needed to achieve Sustainable Development Goal 2 and the short-term investment needed for emergency food assistance shows that while emergency assistance has increased in recent years, there is significant underfunding of the longer-term investment needs. The shortfall in longer-term funding increases the vulnerability to shocks, pushing the number of people affected by hunger and poverty higher. Donors should therefore complement and better link the increased allocation of emergency food assistance with increased investments in longer term agricultural development priorities to prevent future crises when the next shock hits.